2015
DOI: 10.1111/joa.12288
|View full text |Cite
|
Sign up to set email alerts
|

Kohn's pores are not responsible for collateral ventilation between inflated and deflated segments: a microscopic study of pulmonary intersegmental septa in the human lung

Abstract: The composition of the pulmonary intersegmental septum has not been clearly identified by thoracic surgeons who regard Kohn's pores as the main channel that causes air leakage when determining the intersegmental septum by segmental ventilation. In this study, we aimed to examine this possible misinterpretation by focusing on a detailed description of the microscopic anatomy of the intersegmental septum. To accomplish this aim, 50 lung samples of the intersegmental septum from fresh cadavers without emphysema w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Lymph node metastases can appear in the NTB segments, lobes, and even skip metastasis, with regard to lymph drainage on the abnormal anatomy of pulmonary segments. Zuo et al [31] found that pulmonary segmental anatomy was relatively independent, owing to continuous interval segments, with no alveolar hole sections. We hypothesized that tumors invading adjacent parenchyma across the interval would be hindered and that the interval might shut down the spread pathway of spread for tumor cells along the alveolar hole.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastases can appear in the NTB segments, lobes, and even skip metastasis, with regard to lymph drainage on the abnormal anatomy of pulmonary segments. Zuo et al [31] found that pulmonary segmental anatomy was relatively independent, owing to continuous interval segments, with no alveolar hole sections. We hypothesized that tumors invading adjacent parenchyma across the interval would be hindered and that the interval might shut down the spread pathway of spread for tumor cells along the alveolar hole.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact contribution of each of the possible anatomic pathways of collateral ventilation (pores of Kohn, Martin's and Lambert's channels) to gas exchange in both normal and disease states is unknown, the physiologic studies in which collateral ventilation was affected by a hypoxic and hypercarbic stimulus, as well as pharmacologic agents, suggest that Martin's and Lambert's channels and the intersegmental bronchioles are the effective collateral channels in normal lungs (30). These observations are supported by evidence on microscopy that no pores of Kohn exist in intersegmental septa (31).…”
Section: Physiology Of Collateral Ventilationmentioning
confidence: 95%
“…There have been many terminologies which have described the boundary between lung segments, 18 , 19 such as the intersegmental line, intersegmental septum, intersegmental fissure, and intersegmental plane. Each of these terms is a different understanding of the boundary in different perspective or dimension.…”
Section: Discussionmentioning
confidence: 99%